The Influence Of Brand Image And Product Quality On Customer Loyalty At Bintang Motor Manna, South Bengkulu Regency - Tanama, Roki; Hanila , Siti; Abi, Yudi Irawan (Journal of Accounting and Management, 2025)
In the current increasingly tight business competition conditions, companies need to utilize their resources optimally, including trying to create or engineer things that can influence consumer perceptions, for example through the brand image of their products. The purpose of this study is to prove that brand image and product quality have an effect on customer loyalty at Bintang Motor Manna Bengkulu Selatan. The analysis method in this study uses Validity Test, Reliability Test, Multiple Linear Regression Analysis, Determination Coefficient, and hypothesis testing using t-test and f-test with the number of samples studied 50 customers at the Bintang Motor Manna Store. From the calculation results using SPSS 24, we can see that brand image and product quality have a significant effect on customer loyalty. In this case, the significance value of variable X <0.05 is 0.001.  The results of the multiple linear regression analysis are the equation Y = 10.453 + 0.393 X1 + 0.376 X2, this illustrates a positive regression direction, meaning that the brand image variable (X1) and product quality (X2) have a positive influence on customer loyalty (Y) at the Bintang Motor Manna Shop, South Bengkulu. From the calculation results using SPSS, the determination coefficient value of R square can be seen as 0.654. ​​This means that the value of Brand Image (X1) and the value of Product Quality (X2) have an effect on Customer Loyalty (Y) of 65.4% while the remaining 34.6% is influenced by other variables not examined in the study.